2014
DOI: 10.1002/jbmr.2320
|View full text |Cite
|
Sign up to set email alerts
|

Bone Regeneration With Osteogenically Enhanced Mesenchymal Stem Cells and Their Extracellular Matrix Proteins

Abstract: Although bone has remarkable regenerative capacity, about 10% of long bone fractures and 25–40% of vertebral fusion procedures fail to heal. In such instances, a scaffold is employed to bridge the lesion and accommodate osteoprogenitors. Although synthetic bone scaffolds mimic some of the characteristics of bone matrix, their effectiveness can vary due to biological incompatibility. Herein, we demonstrate that a composite prepared with osteogenically enhanced mesenchymal stem cells (OEhMSCs) and their extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 40 publications
5
68
0
1
Order By: Relevance
“…Recently, we confirmed that OEhMSCs do not inherently activate proliferation of immunologically mismatched lymphocytes [52], but it was unclear whether lymphocyte exposure had a detrimental effect on OEhMSC viability. To address this question, GFP-labeled OEhMSCs were attached to BGS and exposed to immunologically mismatched PBMNCs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, we confirmed that OEhMSCs do not inherently activate proliferation of immunologically mismatched lymphocytes [52], but it was unclear whether lymphocyte exposure had a detrimental effect on OEhMSC viability. To address this question, GFP-labeled OEhMSCs were attached to BGS and exposed to immunologically mismatched PBMNCs.…”
Section: Resultsmentioning
confidence: 99%
“…Osteogenically enhanced human mesenchymal stem cells were generated by culture for 8 days in the presence of 10 μM GW9662 and osteogenic supplementation, as previously described [5052]. …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations